Overdiagnosis: what it is and what it isn't. - Brodersen, J; Schwartz, L; Heneghan, C; O'Sullivan, J; Aronson, J; Woloshin, S (BMJ Publishing Group, 2018)
Rosalind’s question, as she is about to marry Orlando, is purely rhetorical—she thinks that one cannot desire too much of a good thing. Nevertheless, trite though it may be, it is true that one can sometimes have it. It is certainly true of healthcare and has been referred to as ‘too much medicine’,1 although because of potential confusion with ‘too much medication’ a better term might be ‘too much healthcare’. This includes too much screening of asymptomatic individuals, too much investigation of those with symptoms, too much reliance on biomarkers, too many quasi-diseases, too much diagnosis, often leading to too much treatment, sometimes cost-ineffective, medicines that are too costly and too rapidly approved for marketing, too many adverse reactions, and too much inappropriate monitoring. And too much healthcare implies too little effective healthcare.